Institutional policy factors and learners' academic achievement in two open distance learning institutions in Nigeria (2021)
The paper examined the influence of institutional policy factors on learners' academic achievement in National Open University of Nigeria (NOUN) and Distance Learning Centre (DLC), University of Ibadan. The institutional policy factors used for the study were learner supports services, course material development, information communication technology, staff capacity development, quality assurance and feedback method while learners' academic achievement was measured based on cumulative grade performance average records. The population comprised distance learners of 200 to 500 cohorts in the institution with sample size: NOUN -1,120 and DLC – 636. The instrument used for data collection was an Adapted Course Experience Questionnaire Scales developed by graduate careers Australia 2009 of Learner Support Services (r=0.86), Course Material Development ( r=0.84) , Informa t ion Communication Technology(r=0.83), Staff Capacity Development (r=0.80), Quality Assurance(r=0.78), Feedback Method(r=0.75). Data obtained were analysed through descriptive statistics and Multiple regression analysis at 0.05 level of significance. The findings of the study revealed that the Institutional policies significantly influenced students' academic achievement (F(6.1388) =499.75;R2 =0.68), and jointly accounted for 68.2% of its variance. Based on the findings, it was recommended that the management and staff of distance learning institutions should ensure effective implementation of these policies inorder to assist and improve learners' academic achievement. This paper, therefore, concluded that it is pertinent to note that the institutional policy factors implemented by the two institutions to a large extent played significant role in learners' academic achievement.